Customer’s Satisfaction towards ATM Service Quality: A Case of Kathmandu Valley - Mainali, Nabina (Nepalese Journal of Finance, 2025)
This study examines the impact of customer’s satisfaction towards ATM service in Kathmandu Valley. Customer satisfaction is the dependent variable. The selected independent variables are ATM service quality, perceived ease of use, perceived accessibility, expected speed delivery, expected control and reliability and efficiency expected environment. The primary source of data is used to assess the opinions of respondents regarding ATM service quality, perceived ease of use, perceived accessibility, expected speed delivery, expected control and reliability and efficiency expected environment. The study is based on primary data of 151 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of customer’s satisfaction towards ATM service in Kathmandu Valley. The study showed a positive impact of ATM service quality on customer satisfaction. It indicates that better the ATM service quality, better would be the customer satisfaction. Similarly, the study showed a positive impact of perceived ease of use on customer satisfaction. It indicates that the perceived ease of use leads to increase the customer satisfaction. The study also revealed a positive impact of perceived accessibility on customer satisfaction. Furthermore, it indicates that higher the perceived accessibility, higher would be the customer satisfaction. Likewise, the study observed a positive impact of expected speed delivery on customer satisfaction. Likewise, it indicates that higher the expected speed delivery, higher would be the customer satisfaction. Similarly, the study observed a positive impact of expected control on customer satisfaction. However, it indicates that expected control of employee leads to increase in employee commitment. Similarly, the study showed a positive impact of reliability on customer satisfaction. It indicates that higher the reliability, higher would be the customer satisfaction.